Gene replacement therapy restores RCBTB1 expression and cilium length in patient‐derived retinal pigment epithelium - Huang, Zhiqin; Zhang, Dan; Chen, Shang‐Chih; Jennings, Luke; Carvalho, Livia S.; Fletcher, Sue; Chen, Fred K.; McLenachan, Samuel (Journal of cellular and molecular medicine, 2021)
Biallelic mutations in the RCBTB1 gene cause retinal dystrophy. Here, we characterized the effects of RCBTB1 gene deficiency in retinal pigment epithelial (RPE) cells derived from a patient with RCBTB1‐associated retinopathy and restored RCBTB1 expression in these cells using adeno‐associated viral (AAV) vectors. Induced pluripotent stem cells derived from a patient with compound heterozygous RCBTB1 mutations (c.170delG and c.707delA) and healthy control subjects were differentiated into RPE cells. RPE cells were treated with AAV vectors carrying a RCBTB1 transgene. Patient‐derived RPE cells showed reduced expression of RCBTB1. Expression of NFE2L2 showed a non‐significant reduction in patient RPE cells compared with controls, while expression of its target genes (RXRA, IDH1 and SLC25A25) was significantly reduced. Trans‐epithelial electrical resistance, surface microvillus densities and primary cilium lengths were reduced in patient‐derived RPE cells, compared with controls. Treatment of patient RPE with AAV vectors significantly increased RCBTB1, NFE2L2 and RXRA expression and cilium lengths. Our study provides the first report examining the phenotype of RPE cells derived from a patient with RCBTB1‐associated retinopathy. Furthermore, treatment of patient‐derived RPE with AAV‐RCBTB1 vectors corrected deficits in gene expression and RPE ultrastructure, supporting the use of gene replacement therapy for treating this inherited retinal disease.